2012
DOI: 10.1111/j.1542-4774.2012.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Education, Home Environments, and the Development of Children and Adolescents

Abstract: We study the intergenerational effects of maternal education on children's cognitive achievement, behavioral problems, grade repetition and obesity. We address endogeneity of maternal schooling by instrumenting with variation in schooling costs when the mother grew up. Using matched data from the female participants of the National Longitudinal Survey of Youth 1979 (NLSY79) and their children, we can control for mother's ability and family background factors. Our results show substantial intergenerational retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
240
5
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(272 citation statements)
references
References 72 publications
(110 reference statements)
19
240
5
8
Order By: Relevance
“…Moreover, children’s Internet addiction showed a strong correlation with mother’s high education level when their mother had depression. Previous study found that mothers who had high education level provide better home environment for their children by educating musical instruments, special lessons, and books [27]. When high educated mother got depressed, it would be difficult to support their children compared to those who did not get depressed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, children’s Internet addiction showed a strong correlation with mother’s high education level when their mother had depression. Previous study found that mothers who had high education level provide better home environment for their children by educating musical instruments, special lessons, and books [27]. When high educated mother got depressed, it would be difficult to support their children compared to those who did not get depressed.…”
Section: Discussionmentioning
confidence: 99%
“…Following this finding, the nonsignificant relation between children’s mothers holding a master’s degree (i.e., an even higher level of education) and their science content knowledge found in this study is paradoxical and surprising. One possible explanation is that more educated mothers such as those who have a master’s degree may be more likely to work and work for more hours (Carneiro, Meghir, & Parey, 2013). They may not provide more learning opportunities than those mothers who hold only a bachelor’s degree.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are involuntary increases in schooling for a group who are likely to be drawn from those with lower prior educational attainment and a less positive attitude toward education. Other IV strategies which focus on unanticipated variations in opportunities for continuing education to the graduate level, such as Carneiro et al (2008), are likely to be drawing inference from a very different part of the educational attainment distribution and there is no a priori reason why the effects should be similar across these groups. The 'local average treatment effect' identified at the low education part of the distribution is likely to be more important in policy terms where policy makers are concerned with low intergenerational mobility or low income in the second generation.…”
Section: Instrumental Variable Studiesmentioning
confidence: 99%
“…There have been a number of recent studies using a range of techniques to isolate the causal effect of parental education (see Holmlund et al, 2011, for a reconciliation study for the main techniques used). Oreopoulos et al (2006), Chevalier (2004), Black et al (2005), Chevalier et al (2005), Carneiro et al (2008) and Maurin and McNally (2008) and all use instrumental variables techniques with a variety of instruments and with quite diverse results. Few studies go on to assess the age at which the intergenerational education transmission emerges and the relative scale of effects across literacy and numeracy.…”
mentioning
confidence: 99%